Attitudes and knowledge for CBT-based psychotherapy among medical students and residents in China: a survey study - Yinan Ding; Tao Pei; Pu Peng; Jiashu Yao; Jinsong Tang; Yanhui Liao (BMC Medical Education)
Abstract Background/aim Psychotherapy training for medical students and residents in China is still in development. To establish an appropriate training program, understanding medical students’ and residents’ current knowledge and attitudes toward psychotherapy is needed. Methods One hundred and forty-nine participants, including medical students, residents, and other health providers (HCPs), self-reported their understanding of 18 types of psychotherapy, negative attitude towards cognitive behavioral therapy (CBT), and their attitude towards psychological interventions and counseling in primary care (APIC-PC) through an online survey. Results Participants’ understanding of psychotherapy was generally low (M = 26.25, SD = 22.99). Medical students’ (M = 34.42, SD = 22.61) and HCPs’ (M = 37.25, SD = 30.834) understanding was significantly higher than residents’ (M = 20.08, SD = 19.54), F(2, 146) = 8.63, p < .001. Participants from psychiatric departments (M = 33.85, SD = 25.89) understood more psychotherapy than those from non-psychiatric departments (M = 20.98, SD = 19.20), t(147) = 3.46, p < .001. Participants with a bachelor’s degree (M = 2.40, SD = 0.976) scored lower on the Negative Attitude Towards CBT Scale than participants with a graduate degree (M = 2.76, SD = 1.00), t(147) = -2.20, p = 0.029. All participants’ APIC-PC scores were relatively the same and indicated a neutral to slightly positive attitude towards psychotherapy and counseling practices. However, they showed a slightly negative attitude in the “willingness to counsel” subscale (M = 2.65, SD = 0.93). Conclusion This study indicated a lack of knowledge of psychotherapy and a lack of psychotherapy courses for medical students and residents, especially those from non-psychiatric departments in China. Our findings suggest an urgent need for psychotherapy and relevant training for Chinese medical students and residents. Trial registration The study has been registered at ClinicalTrials.gov (Identifier: NCT06258460, website: httpsregister.clinicaltrials.gov ).